Influência da morfina, fentanil e tramadol na concentração anestésica mínima do isofluorano em papagaios-verdadeiros (Amazona aestiva) - Cunha, Laura Gabriela da (2013)
Recently, the demand for assistance of wild birds has increased in Brazil, but there few scientific reports on analgesia regarding this animal class. Inhalational anesthesia is an alternative widely used in birds and it is considered the safest for this class. However, one of its disadvantages is having a Minimum Anesthetic Concentration (MAC) very close to the anesthetic index.The use of balanced anesthesia stands out for promoting positive results such as fewer adverse reactions to hemodynamic stability; for instance, the use of opioid agents combined with inhalational anesthesia. Assessment of the side effects of anesthesia in birds has been carried out in two different ways: liberating electrical and/or thermal stimulus on conscious birds at bipedal position, either on perches or plates; or through the determination of the MAC of inhalational anesthetics. The purpose of this study was to evaluate the effect of isoflurane combined with an opioid on the cardiorespiratory system and to demonstrate the MAC of inhalational anesthetics. To this end, 24 healthy blue-fronted parrots (Amazona aestiva) from the Zoological Park of the Federal University of Mato Grosso – UFMT were used. The day before the experiment, the birds were placed in cages and underwent a four-hour solid and water fast. After physical restraint, the birds were anesthetized with 3.5V% isoflurane; as soon as proper muscle relaxation and loss of consciousness were observed, orotracheal intubation was performed and inhalational analgesia was reduced to 1.5V% concentration. A time period of 15 min was observed for anesthesia stabilization, then the birds were submitted to nociceptive stimulus by digital pressure at the second digit; this procedure was held for one minute. When negative response to nociceptive stimulus was verified, the inhalational anesthetic concentration was reduced by 20% while waiting for anesthesia stabilization, then a new stimulus was performed, and so on, until positive response (sudden movements such as flapping of wings, lifting of head, or abrupt bending of knees) was verified, when the anesthetic concentration was then increased by 10% at each positive response until a new negative response was observed, when the inhaled air concentration level was recorded as the MAC of the isoflurane for that individual. The same experimental procedure was carried out for 15 days, with the birds randomly divided in three groups to which morphine (1 mg/kg), fentanyl (0.03 mg/kg), or tramadol (12 mg/kg) was administered intramuscularly. After the application of the drugs and anesthesia stabilization, the determination of the MAC was conducted identically as performed for the isoflurane. The MAC values of the treatments were similar to the MAC values of the isoflurane and, in the same way, there were no significant alterations, comparatively, in the physiological variables, cardiac and respiratory frequencies, systolic blood pressure, and CO2 concentrathion in the exhaled air. It was possible to conclude that the opioids, in the doses given, did not produce analgesia in the species at issue. Further research is needed in order to determine adequately the particularities of use for each bird species